Pengaruh Kualitas Audit Terhadap Kualitas Pelaporan Keuangan Perusahaan dengan Efektivitas Komite Audit Sebagai Variabel Moderasi - Aini, Talitha Nur; Prasetyo, Andrian Budi (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2023)
This research aims to examine The Effect of Audit Quality on Corporate Financial Reporting Quality with Audit Committee Effectiveness as a Moderating Variable. The population of the research are manufacturing companies listed on the Indonesia Stock Exchange in 2016-2019. The sample of this study consisted of 36 companies (144 annual reports) listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 period. The data used in this study were secondary data and the sample selection using purposive sampling method. The analysis model uses multiple linear analysis. The results explain that audit quality as measured by KAP size, audit fees, and audit tenure significantly affect the quality of the company's financial reporting. And the effectiveness of the audit committee strengthens the relationship between audit quality as measured by the size of KAP, audit fees, and audit tenure on the quality of the company's financial reporting.